Spatial Solar Energy Potential of Photovoltaic Panels Surrounded by Protected Mountain Ranges - Stachura, Tomasz; Halecki, Wiktor; Belda, Dawid; Chmielowski, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
High growth of human population and dynamic socio-economic development have contributed to mounting demand for electric energy. Currently, electric energy is mainly generated from mined and combusted fossil fuels and by the nuclear power plants. The current geopolitical crisis forces mankind to reflect upon the search for alternative energy sources. In this paper analyses of the potential solar radiation volume for 12 months and annual total have been made and visualized on the maps.
Keywords: carbonless policy; GIS-based assessment; photovoltaic panels; total solar radiation; green energy; polityka bezemisyjna; ocena oparta na GIS; panele fotowoltaiczne; całkowite promieniowanie słoneczne; zielona energia